2015
DOI: 10.1371/journal.pone.0135495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cinnamon Oil on Quorum Sensing-Controlled Virulence Factors and Biofilm Formation in Pseudomonas aeruginosa

Abstract: Quorum sensing (QS) is a system of stimuli and responses in bacterial cells governed by their population density, through which they regulate genes that control virulence factors and biofilm formation. Despite considerable research on QS and the discovery of new antibiotics, QS-controlled biofilm formation by microorganisms in clinical settings has remained a problem because of nascent drug resistance, which requires screening of diverse compounds for anti-QS activities. Cinnamon is a dietary phytochemical tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 43 publications
6
85
0
2
Order By: Relevance
“…The most prominent activity was observed with S. jambos and S. antisepticum extracts. In the earlier study, a similar effect in the pigment production by C. violaceum was observed when treated with cinnamon oil , the extracts of Cuminum cyminum and Kigelia africana fruit .…”
Section: Discussionsupporting
confidence: 74%
“…The most prominent activity was observed with S. jambos and S. antisepticum extracts. In the earlier study, a similar effect in the pigment production by C. violaceum was observed when treated with cinnamon oil , the extracts of Cuminum cyminum and Kigelia africana fruit .…”
Section: Discussionsupporting
confidence: 74%
“…Cinnamon oil has various antibacterial properties. It has potent activity against Pseudomonas aeruginosa and E. coli O157:H7 biofilms (Kalia et al ., ; Kim et al ., ). The active component cinnamaldehyde inhibits multi drug resistant strains of P. aeruginosa (Utchariyakiat et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…This result was similar to that of Tong and Bloomquist (2013), who found that several plant essential oils show significant synergistic effects with carbaryl. Cinnamon oil has been used in several toothpastes as an antimicrobial substitute (Kalia et al 2015). Thus, this oil is relatively safe for human consumption.…”
Section: Discussionmentioning
confidence: 99%